Gangland Gotham: New York's notorious mob bosses - May, Allan R. (Greenwood Press, 2009)
Joe Adonis (Giuseppe Antonio Doto) -- Albert Anastasia (Umberto Anastasio) -- Louis Buchalter -- Frank Costello (Francesco Castiglia) -- Carlo Gambino -- Vito Genovese -- Lucky Luciano (Salvatore Lucania) -- Arnold Rothstein -- Dutch Schultz (Arthur Flegenheimer) -- Abner Zwillman